Temporal dynamics of Plasmopara viticola as function of bud load increase in ‘Sauvignon Blanc’ Dinâmica temporal de Plasmopara viticola em função do aumento da carga de gemas em ‘Sauvignon Blanc’ - Wurz D.A. (2023)
© (2023), (Embrapa). All Rights Reserved.The objective of this work was to evaluate the effect of increasing bud load per plant on epidemiological variables of downy mildew on ‘Sauvignon Blanc’. The study was carried out in a commercial vineyard in a high-altitude region of the municipality of São Joaquim, in the state of Santa Catarina, Brazil, during the 2016/2017 and 2017/2018 vintages. The treatments consisted of four bud loads: 15, 30, 50, and 75 per vine. The maximum incidence, maximum severity, beginning of symptom appearance, time to reach maximum disease incidence and severity, area under the incidence and severity disease progress curve were determined. Increasing bud load over 50 per vine results in higher incidence and severity of downy mildew (Plasmopara viticola) in ‘Sauvignon Blanc’ leaves but does not influence the time to reach maximum disease incidence and severity. Increasing bud load over 50 per vine results in an increase in the area under the disease incidence and severity progress curve for downy mildew in ‘Sauvignon Blanc’ leaves. To adopt over 50 buds per vine treatment, it is necessary additional disease control measures, with an emphasis on integrated management to control downy mildew.